The Influence of Empowering Leadership on the Affective Commitment of General Hospital Employees with Psychological Empowerment as Mediator Variables - Listiyowati, Listiyowati; Suryanto, Suryanto; Santi, Dyan Evita (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this research is to analyze the influence of empowering leadership on affective commitment through psychological empowerment as a mediator for General Hospital (RSU) employees. Sampling was 180 employees using total sampling technique. Data was collected using the affective commitment scale by Lunthans (2005), the empowering leadership scale by Konczak, et al (2000). The Psychological Empowerment Questionnaire (PEQ) scale was developed by Spreitzer (1995). The analysis technique uses path analysis using PLS.3.0. In the results of the direct effect test, the value obtained was p = 0.000 < 0.05, it can be concluded that there is an influence between empowering leadership and psychological empowerment. The second hypothesis, obtained p value = 0.009 < 0.05, it can be concluded that there is an influence between psychological empowerment and affective commitment. The third hypothesis, obtained p value = 0.000 < 0.05, it can be concluded that there is a positive influence between empowering leadership on affective commitment. The fourth hypothesis (p = 0.026 < 0.05) suggests that empowering leadership influences affective commitment in Public Hospital personnel through psychological empowerment.